Teaching Style in Physical Education and Changes of Daily Physical Activity after One Academic Year in Adolescents: GEOS Study - Martín-Sanz, Norma T.; López-Fernández, Iván; Chinchilla-Minguet, José Luis; Álvarez-Carnero, Elvis (My University, 2015)
Increased Moderate-Vigorous physical activity (MVPA) and reduced sedentary time (ST) are key factors for a healthy lifestyle during childhood and adolescence. Studies have suggested that schools may be effective resources to promote healthy habits (Sallis, McKenzie et al. 2012). Therefore, in PE, is important to assess how teachers use strategies and provide students tools to engage in PA with the purpose of reduce the risk of sedentary behavior and contribute to promotion MVPA habits for a healthy lifestyle (Lonsdale, C. et al., 2013). Many factors may be involved in the successful PE class to promote healthy out-school behaviors, as teaching styles (TS), learning styles, learning time, motivation and so on (Mosston, M. 1966). Regarding TS, there is a lack of knowledge about influence of the teaching style (TS) in the promotion of daily MVPA. It was our aim to observe the differences of total daily PA dimensions between two groups of adolescents who were taught during a whole academic year using reproducing (RK) or producing knowledge (PK) TSs.
Keywords: Educación física para niños